2006
DOI: 10.1093/eurheartj/ehl098
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillatory rate and sinus rhythm maintenance in patients undergoing cardioversion of persistent atrial fibrillation

Abstract: In patients undergoing cardioversion of persistent AF, AF relapse is predicted by a higher AFR. A stronger association is seen in patients with short arrhythmia duration, reflecting either rapid remodelling or pre-existing changes in those who relapse to AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 36 publications
8
51
2
1
Order By: Relevance
“…[1], [5], [6] and [22] However, as in earlier observations from our group studying AFR as an index of atrial remodeling, the overlap between patients maintaining SR and those not maintaining SR is extended. 5 In the present study, the performance of AFSE and AFR was virtually identical.…”
Section: Indices Of Electrical Remodeling and Sr Maintenancementioning
confidence: 83%
See 3 more Smart Citations
“…[1], [5], [6] and [22] However, as in earlier observations from our group studying AFR as an index of atrial remodeling, the overlap between patients maintaining SR and those not maintaining SR is extended. 5 In the present study, the performance of AFSE and AFR was virtually identical.…”
Section: Indices Of Electrical Remodeling and Sr Maintenancementioning
confidence: 83%
“…[1], [5], [6] and [22] However, as in earlier observations from our group studying AFR as an index of atrial remodeling, the overlap between patients maintaining SR and those not maintaining SR is extended. 5 In the present study, the performance of AFSE and AFR was virtually identical. Previous studies have shown slightly better performance of AFSE when discriminating paroxysmal from persistent AF [2] and [6] and predicting SR maintenance following cardioversion.…”
Section: Indices Of Electrical Remodeling and Sr Maintenancementioning
confidence: 83%
See 2 more Smart Citations
“…for the prediction of electrical cardioversion outcome for AF. However, very different and, consequently, inconclusive results have been obtained [10]. Thereby, the aim of this work is to obtain a new robust and non-invasive predictor of NSR maintenance after ECV before it is attempted.…”
Section: Introductionmentioning
confidence: 99%